Stimuli-responsive hydrogel dressing for wound healing - Wei Zhang; Jun Hu; Hao Wu; Xiufei Lin; Limei Cai (APL Materials)
Wound healing is a complex, variable, and time-dynamic repair process. Wounds can be classified as acute wounds or chronic wounds, and effective wound management is still a major challenge in clinical nursing settings. The wound microenvironment is collectively regulated by internal biomolecules, external drugs, and external sanitation. Traditional wound dressings (powders, bandages, sponges, etc.) often have poor therapeutic effects during wound healing and repair processes because they cannot respond to the dynamic wound microenvironment changes over the long-term. Stimulus-responsive biomaterials, which are activated by various factors intrinsic to the wound microenvironment or external influences, hold great promise for precise drug delivery and controlled release. Various stimulus-responsive hydrogels have been developed in recent years, exhibiting a range of “smart” properties, such as interacting with the wound, sensing wound conditions or environmental changes, and responding accordingly, thereby effectively promoting wound healing. This review discusses the latest advancements in stimulus-responsive hydrogels used in wound healing. We introduce the design scheme of stimulus-response hydrogels in detail based on the local wound biological/biochemical peculiarities (pH, reactive oxygen species glucose, and enzymes, etc.) and physical microenvironments (temperature, light, ultrasound, and electric fields, etc.). Furthermore, we explore several promising tissue-engineered constructs (nanofibers, scaffolds, microneedles, and microspheres). Finally, summarize stimulus-responsive wound dressings on the basis of active research challenges, current research progress, and development trends in the field.